Effectiveness of Cooperative Learning: “Give One Get One” in Procedure Text Reading - Duwi Nur Vadila; Wulan Dari, Retno (English Department, Universitas Negeri Surabaya, 2024)
Reading comprehension is a fundamental skill for academic success, yet many students struggle with understanding complex texts, particularly procedural texts, which require sequential comprehension. This study investigates the effectiveness of the Give One Get One (GOGO) strategy in improving students’ reading comprehension of procedure texts. The study employs a quantitative research method using a one-group pre-test and post-test design to measure students’ progress. A total of 32 senior high school students participated in the study. Students underwent three treatment sessions, with their reading comprehension assessed before and after the intervention. The findings indicate that while there was a statistically significant difference in students’ reading comprehension scores, the effect size was very weak. Post-test results showed that some students’ scores declined, suggesting that the GOGO strategy may not be effective for teaching procedural texts. The structured nature of procedure texts may have limited the interactive benefits of the strategy, leading to inconsistent improvements in student performance. These results highlight the need for educators to carefully select instructional strategies based on text type and learning objectives. While GOGO may be effective for certain text genres, it may require modification or supplementation when applied to structured texts like procedural writing. Further research should explore alternative strategies that enhance engagement while maintaining comprehension accuracy.